INOVASI PROGRAM PARIKESIT (PARIWISATA KESEHATAN PUSKESMAS MIROTO) DALAM MENINGKATKAN JUMLAH KUNJUNGAN ANAK PG-TK DI UPTD PUSKESMAS MIROTO KOTA SEMARANG - Fariska Karima mufaiqoh; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
The low utilization of dental health services despite the high prevalence of oral health problems indicates a substantial gap between healthcare needs and service use. In the working area of UPTD Puskesmas Miroto, this gap is evident in the large number of potential targets among playgroup and kindergarten (PG–TK) children, which is not reflected in the relatively low number of dental clinic visits. In response to this issue, the PARIKESIT Program (Health Tourism Program of Miroto Community Health Center) was introduced as an innovation based on the Decree of the Head of the Semarang City Health Office No. 440/0183/A concerning the establishment of innovation programs at UPTD Puskesmas Miroto to optimize schoolchildren’s health efforts. This study aims to analyze the effectiveness of the PARIKESIT Program (Health Tourism Program of Miroto Community Health Center), as well as to identify the driving and inhibiting factors affecting the program’s effectiveness in increasing the number of playgroup kindergarten (PG-TK) children's visits to the dental clinic at the Miroto Community Health Center. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Informants were selected using purposive sampling, while data quality was ensured through source triangulation. The results indicate that the effectiveness of the PARIKESIT Program innovation in increasing the number of PG TK children's visits at the Miroto Community Health Center is categorized as less effective. Although there has been a consistent annual increase in visits from PG-TK children and a growing number of young patients who continued treatment after their first visit to the dental clinic following the program’s implementation, several aspects remain suboptimal. In practice, the integration aspect has not been implemented effectively, and the frequency of program implementation remains very limited. Other inhibiting factors include limited human resources and the absence of a dedicated budget allocation for the program.